Public Hospital - Najem, Meqdad (My University, 2017)
Project Name: Public Hospital. Location: Sahl Rougeb , east of Nablus. Project area : 22000 Sqm. The concept : In order to change the stereotype of hospitals and improve the psychological state of The patients i have designed a huge green courtyard in the middle of the hospital so that all the unites are directed towards it .